Programmatic Variation in Home Hemodialysis in Canada: Results from a Nationwide Survey of Practice Patterns. Issue 1 (10th June 2014) - Pauly, Robert P; Komenda, Paul; Chan, Christopher T; Copland, Michael; Gangji, Azim; Hirsch, David; Lindsay, Robert; MacKinnon, Martin; MacRae, Jennifer M; McFarlane, Philip; Nesrallah, Gihad; Pierratos, Andreas; et al.
Background: Over 40% of patients with end stage renal disease in the United States were treated with home hemodialysis (HHD) in the early 1970's. However, this number declined rapidly over the ensuing decades so that the overwhelming majority of patients were treated in-centre 3 times per week on a 3–4 hour schedule. Poor outcomes for patients treated in this fashion led to a renewed interest in home hemodialysis, with more intensive dialysis schedules including short daily (SDHD) and nocturnal (NHD). The relative infancy of these treatment schedules means that there is a paucity of data on 'how to do it'. Objective: We undertook a systematic survey of home hemodialysis programs in Canada to describe current practice patterns. Design: Development and deployment of a qualitative survey instrument. Setting: Community and academic HHD programs in Canada. Participants: Physicians, nurses and technologists. Measurements: Programmatic approaches to patient selection, delivery of dialysis, human resources available, and follow up. Methods: We developed the survey instrument in three phases. A focus group of Canadian nephrologists with expertise in NHD or SDHD discussed the scope the study and wrote questions on 11 domains. Three nephrologists familiar with all aspects of HHD delivery reviewed this for content validity, followed by further feedback from the whole group. Multidisciplinary teams at three sites pretested the survey and further suggestions were incorporated. In July 2010 we distributed the survey electronically to all renal programs known to offer HHD according to the Canadian Organ Replacement Registry. We compiled the survey results using qualitative and quantitative methods, as appropriate. Results: Of the academic and community programs that were invited to participate, 80% and 63%, respectively, completed the survey. We observed wide variation in programmatic approaches to patient recruitment, human resources, equipment, water, vascular access, patient training, dialysis prescription, home requirements, patient follow up, medications, and the approach to non-adherent patients. Limitations: Cross-sectional survey, unable to link variation to outcomes. Competition for patients between HHD and home peritoneal dialysis means that case mix for HHD may also vary between centres. Conclusions: There is wide variation between programs in all domains of HHD delivery in Canada. We plan further study of the extent to which differences in approach are related to outcomes.